(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2017)
The marketplace has always been a key space for cities, not only for commercial purposes, but also and mostly as an enabler of cultural and social exchange. With the advent of new technologies and the virtualisation of many everyday activities, particularly social activities such as shopping and communicating, many physical spaces could be at risk of decaying and even disappearing, in favour of online platforms. One of this physical spaces is the marketplace. However, rather than decaying, in recent years many markets have been refurbished and others have flourished, carpeting many contemporary western cities. The marketplaces that are blossoming not only provide trade exchange, but enable users to gather together and, by offering many food-based activities, attract people to stay and engage. This paper investigates this contemporary urban phenomenon by looking at the history of the marketplace, the intrinsic relationship between food and cities, and by analysing the city of Madrid and its market-boom as the main case study.